The weight for length in late preterm infants assessed with bioelectrical impedance is positively associated with anthropometric variables - Elisabet Gómez Santos; Francisco José López Lorente; José Ramón Fernández Fructuoso; Pedro Cortés Mora; Carmen Fuentes Gutiérrez; Vicente Bosch Giménez (Anales de Pediatría (English Edition), 2023)
Introduction: The fat mass (FM) is greater in late preterm than full term infants at 1 month post birth, which may be an additional risk factor for metabolic syndrome in adulthood. Objetives: To evaluate body composition (BC) in late preterm infants using bioelectrical impedance analysis (BIA) to determine which anthropometric parameters are associated with BC. Our hypothesis was that weight-for-length is associated with the length-normalized fat mass index (FMI) at 1 year of life. Materials and methods: We carried out a prospective cohort study in 2 groups: late preterm infants and full term infants. We obtained BC data by BIA. We calculated the fat mass (FM), FMI, fat-free mass (FFM) and length-normalized fat-free mass index (FFMI) at 1, 6 and 12 months of life. After, we assessed the association of the FMI with anthropometric parameters using multiple linear regression analysis. Results: The study included 97 late preterm and 47 full term infants, although at 12 months of life, the BC assessment was performed on 66 and 33 infants, respectively. Late preterm infants, compared to full term infants, had a higher FFM at 1 month (4013 vs 3524 g), a higher weight velocity at 6 months (5480 g versus 4604 g) and a lower FFM (7232 vs 7813 g) and FFMI (12.55 vs 13.26) at 12 months of life. The multivariate regression analysis showed that the weight-for-length z-core at 12 months was positively associated with the FMI at 12 months in all infants. Conclusion: The weight-for-length z-score at 12 months is strongly associated with the FMI at 1 year of life. Further studies are needed to investigate whether an increment in this anthropometric parameter may modulate the risk of chronic diseases. Resumen: Introducción: La masa grasa es mayor en lactantes pretérmino tardíos que en lactantes nacidos a término al mes de vida y esto podría ser un factor de riesgo adicional para el síndrome metabólico en la vida adulta. Objetivos: Para evaluar la composición corporal (CC) en prematuros tardíos utilizamos el análisis de impedancia bioeléctrica (BIA) y buscamos determinar qué parámetro antropométrico está asociado con la CC. Nuestra hipótesis es que el peso para la longitud está asociado con el índice de masa grasa (IMG) normalizado por longitud al año de vida. Materiales y métodos: Realizamos un estudio de cohortes prospectivo con dos grupos: prematuros tardíos y nacidos a término. Los datos de CC se midieron mediante BIA. Se calcularon la masa grasa (MG), el índice de masa grasa (IMG), la masa libre de grasa (MLG) y el índice de masa libre de grasa (IMLG) normalizado por talla a los 1, 6 y 12 meses de vida. Luego determinamos la asociación del IMG con los parámetros antropométricos mediante un análisis de regresión lineal múltiple. Resultados: Incluimos 97 prematuros tardíos y 47 nacidos a término, aunque la evaluación de CC se realizó en 66 y 33 a los 12 meses de vida. Al mes, el contenido de MLG fue mayor en los recién nacidos prematuros tardíos (4013 frente a 3524 g); a los 6 meses, tuvieron una mayor velocidad de incremento de peso (5480 g versus 4604 g) y a los 12 meses de vida, el contenido de MLG y el IMLG de los recién nacidos prematuros tardíos fue menor que el de los recién nacidos a término (7232 versus 7813 g; 12,55 versus 13.26). Según el análisis de regresión multivariable, la puntuación z del peso para la talla a los 12 meses se asoció positivamente con el IMG a los 12 meses en todos los lactantes. Conclusión: La puntuación z del peso para la talla a los 12 meses está estrechamente relacionada con el IMG al año de vida. Se necesitan más estudios para investigar si un incremento en este parámetro antropométrico puede modular el riesgo de enfermedades crónicas.